CHEMISTRY LEARNING INNOVATION WITH RELIGIOUS CHARACTER INTEGRATED REACTION RATE MODULE FOR CLASS XI STUDENTS OF SENIOR HIGH SCHOOL - Ratna Kumala Dewi; Ummi Khusniatil Khofifah; Nur Azzanizawaty Binti Yahya (Fenomena, 2022)
Chemistry learning activities for high school students to make it more attractive can be done with learning media innovations. The appropriate learning media to be applied at this time is blended learning-based media. One of the characteristics that need to be developed in the blended learning model is religious character. The religious character in chemistry lessons can be related to the verses in the Qur'an, one of which is the material on the rate of reaction. The purpose of this study was to determine the effectiveness of the module, student responses, and the feasibility of the module for class XI students on the reaction rate material. This research method uses R&D ( Research and Development) Borg & Gall. The results showed that the validation test of the integrated reaction rate module of religious characters showed a very high value with an average material score of 87.6% and media of 89%. In the small-scale trial, the results of student responses to the integrated module with religious character were categorized as very feasible. Based on the results of the discussion, it can be concluded that the reaction rate module with religious characteristics can be used as an alternative medium for class XI students. Kegiatan pembelajaran kimia untuk siswa SMA agar lebih menarik dapat dilakukan dengan inovasi media pembelajaran. Media pembelajaran yang sesuai untuk bisa diterapkan pada saat ini adalah media berbasis blended learning. Pembentukan karakter yang perlu dikem-bangkan dalam model pembelajaran blended learning salah satunya adalah karakter religius. Karakter religius pada pelajaran kimia dapat dikaitkan dengan ayat yang ada pada Al-Qur'an salah satunya adalah materi laju reaksi. Tujuan penelitian ini adalah untuk mengetahui keefektifan modul, respon siswa, dan kelayakan modul bagi siswa kelas XI pada materi laju reaksi. Metode penelitian ini menggunakan R&D (Research and Development) Borg & Gall. Hasil penelitian menunjukkan bahwa uji validasi modul laju reaksi terintegrasi karakter religius menunjukkan nilai yang sangat tinggi dengan rata-rata skor materi 87,6% dan media 89%. Pada uji coba skala kecil hasil respon tanggapan siswa terhadap modul terintegrasi dengan karakter religius dikategorikan sangat layak. Berdasarkan hasil pembahasan, dapat disimpulkan bahwa modul laju reaksi berkarakter religius dapat digunakan sebagai media alternatif bagi siswa kelas XI.